1985
DOI: 10.1128/jcm.21.5.835-837.1985
|View full text |Cite
|
Sign up to set email alerts
|

Detection of synergistic hemolytic activity of Staphylococcus aureus with the Cathra replicator

Abstract: A replicator method for screening Staphylococcus aureus isolates for synergistic hemolytic activity is described. The technique should also be useful for assessing the hemolytic activity of staphylococci and streptococci on different lots or brands of blood agar because the inoculum and the distances between spot inocula are standardized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Furthermore, hlg is the gene encoding gamma hemolysin in 99.5% of S. aureus isolates (Prevost, 1995), whereas the current study found hlg in 98 (88.28%) of all 111 isolates, which included in twenty-four bacterial species, followed by hlb in 75 (67.57%) and hla in 46 (41.4%) because the platelets and monocytes are more sensitive to alpha hemolysis (Todar, 2005). Moreover, the expression of beta hemolysis on BA is influenced by the concentration of magnesium and the chelating agent in the prepared medium (Boyce, 1985). As a result to the inhibitory effect of agar on gamma hemolysis activity, the rabbit blood agarose was used to detect their activity (Divyakolu et al, 2019).…”
Section: Most Infectious Diseases Were Caused Bymentioning
confidence: 99%
“…Furthermore, hlg is the gene encoding gamma hemolysin in 99.5% of S. aureus isolates (Prevost, 1995), whereas the current study found hlg in 98 (88.28%) of all 111 isolates, which included in twenty-four bacterial species, followed by hlb in 75 (67.57%) and hla in 46 (41.4%) because the platelets and monocytes are more sensitive to alpha hemolysis (Todar, 2005). Moreover, the expression of beta hemolysis on BA is influenced by the concentration of magnesium and the chelating agent in the prepared medium (Boyce, 1985). As a result to the inhibitory effect of agar on gamma hemolysis activity, the rabbit blood agarose was used to detect their activity (Divyakolu et al, 2019).…”
Section: Most Infectious Diseases Were Caused Bymentioning
confidence: 99%